UPAYA MENINGKATKAN HASIL BELAJAR PKN MENGGUNAKAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION PADA SISWA KELAS VI SD NEGERI 020 PANGKALAN BARU KECAMATAN SIAK HULU - Usri Usri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the low learning outcomes of student citizenship education. This research was conducted onclass VI students of SD Negeri 020 Pangkalan Baru. This study aims to improve the learning outcomes of student citizenshipeducation through active learning model learning type role reversal question. From the analysis of data on student learningoutcomes before and after the active learning model, the type of role reversal question, students who completed only 18people or 50%, while students who have not completed as many as 18 people or 50% with classical completeness of 50%.After applying the active learning model of the type of role reversal question in the first cycle, the number of students whocompleted it increased to 26 people or 72.2%, while the incomplete students were 10 people or 27.7% with classicalcompleteness of 72%. In the second cycle, the number of students who completed as many as 35 people or 97.2%, while theunfinished as many as 1 person or 2.7% with classical completeness of 97%. With these results, it can be concluded that byimplementing the active learning model the type of role reversal question can improve the learning outcomes of citizenshipeducation in class VI of the SD Negeri 020 Pangkalan Baru.